A wavelet scattering feature extraction approach for deep neural network based indoor fingerprinting localization - Soro, Bedionita; Lee, Chaewoo (Sensors (Switzerland), 2019)
The performance of an Artificial Neural Network (ANN)-based algorithm is subject to the way the feature data is extracted. This is a common issue when applying the ANN to indoor fingerprinting-based localization where the signal is unstable. To date, there is not adequate feature extraction method that can significantly mitigate the influence of the receiver signal strength indicator (RSSI) variation that degrades the performance of the ANN-based indoor fingerprinting algorithm. In this work, a wavelet scattering transform is used to extract reliable features that are stable to small deformation and rotation invariant. The extracted features are used by a deep neural network (DNN) model to predict the location. The zeroth and the first layer of decomposition coefficients were used as features data by concatenating different scattering path coefficients. The proposed algorithm has been validated on real measurements and has achieved good performance. The experimentation results demonstrate that the proposed feature extraction method is stable to the RSSI variation.
Keywords: Decomposition coefficient; Feature extraction methods; Fingerprinting; Fingerprinting algorithm; Indoor localization; Indoor positioning; Rotation invariant; Scattering transforms; Feature extraction; Fingerprinting; Indoor localization; Indoor positioning; Wavelet scattering